The effect of organizational citizenship behavior (OCB) on employee perfomance at parsintauli mighty works branch Boja Kendal - Teti Susilowati; Muryanto Agus Nuswantoro; Asah Wiari Sidiq (Enrichment : Journal of Management, 2023)
This research aims to determine the effect of OCB and job satisfaction on employee performance.The motive of this observe changed into to research the effect of OCB (Organizational Citizenship Behavior) using three dimensions, specifically altruism (conduct of supporting others), conscientiousness (behavior that exceeds the minimum conditions) and sportsmanship (capability to tolerate without complaining) at the overall performance of personnel at PT. Parsintauli Mighty Work Boja Kendal Branch.The technique used on this research is quantitative. The sampling technique used the census method. The pattern used for this observe were all personnel totaling 37 human beings at PT. Parsintauli Karya Perkasa Twigs Boja. Data analysis strategies the use of SPSS.The effects of the regression equation studies show that the affect of OCB with the indicator of altruism (X1) is zero.312, conscientiousness (X2) is zero.498 and the have an impact on of sportsmanship (X3) is 0.286. The R-Square fee acquired is zero.630 or shows a variation of 63.Zero% of Employee Performance (Y) may be explained by using the unbiased variables in the observe, whilst the ultimate 37.0% is explained through other variables outdoor this studies version.